ANALISIS KEMANDIRIAN DAN EFISIENSI BELANJA DAERAH PERBANDINGAN ANTARA SULAWESI TENGGARA DAN SULAWESI TENGAH - Muhamad Armawaddin (Universitas Muhammadiyah Kendari, 2017)
This study aims to determine the phenomenon of Flypapper Effect on the regional expenditure of regencies / cities in the Provinces of Southeast Sulawesi and Central Sulawesi. This study uses secondary data by observing PAD data, DAU and District / Municipality Expenditure in Southeast Sulawesi and Central Sulawesi during the period 2016-2017. Data analysis used is panel data regression analysis. The results showed that in the period 2016-2017 Flypaper Effect was detected at regional expenditures of regencies / cities in Southeast Sulawesi and Central Sulawesi indicating that in the observation period of Regency / City Government in Southeast Sulawesi and Central Sulawesi there was an inefficient use of regional expenditure funds in proportion which is relatively different. Development financing in the provinces of Southeast Sulawesi and Central Sulawesi is still dependent on transfer funds with Central Sulawesi Province relatively more independent than Southeast Sulawesi. The result of the research is proved in the period 2016-2017 that partially and simultaneously, PAD and DAU have significant influence to the regional expenditure in the Regency and City in Central Sulawesi Province. While in Southeast Sulawesi only DAU has a significant effect on regional expenditure in the same period of observation